IMPLEMENTASI LOGIKA FUZZY UNTUK SISTEM OTOMATISASI PENGATURAN PENGISIAN BATERE PEMBANGKIT LISTRIK TENAGA SURYA - Redaksi Tim Jurnal (Energi & Kelistrikan, 2017)
Solar power plants (PLTS) as power plants that use solar rays to generate electrical energy have a big role in reducing the burden of reducing CO2 emissions. Electrical energy generated by solar panels in the form of direct current (DC / direct current) low voltage. This electrical energy will be collected and stored in a battery (accumulator / battery) through a battery charging controller or so-called solar charge controller that serves as a controller charging process so that the voltage and current are filled to the battery does not exceed the ability batteries or overcharge. This research will make the model of charging the batteries in the Solar Charger Controler by using Mamdani's fuzzy inference logic which is used to adjust the direct current that is charged to the battery and transmitted to the load on the PLTS system. This simulation is expected to be applied to a device that acts as a set of excess filling that is streamed from the solar panel to a fuzzy-based battery. Solar Charger based Fuzzy logic controller can be applied to automatically stop the activity if the voltage in the battery by adjusting the charging function and exemption of current from battery to load.